PEMANFAATAN ABU BROMO SEBAGAI BAHAN BAKU STONEWARE BERKODE KLBR-1 DAN PENGARUHNYA TERHADAP PERHITUNGAN VARIABEL KEUANGAN PADA UPT PSTKP BALI - I Nyoman Normal; Wiryawan Suputra Gumi (STIMI Handayani Denpasar, 2014)
The aims of this research that relate Bromo dust as raw material ofstoneware that Klbr-1 code were : (1) Determine production process; (2) Calculatefinancial variable that follow by: cost of good manufactured and cost price; and (3)Assess marketing mix. The research results that relate Bromo dust as raw materialof stoneware that Klbr-1 code were : (1)Bromo dust could use as raw materialof stoneware after laboratory testing of physical characteristic raw material andwas produce Klbr-1 stoneware. Klbr-1 stoneware composition follow by : noodleKalimantan blend 50%,Bromo dust 20%, sant 20%, Bukit-Jimbaran capur 5%,and Bantur ballclay 5%. The production process of Bromo dust as raw material ofKlbr-1 stonewarefollow by some of stage, tah is : preparing & weighting, grinding,filtrating, firing, deaering, aging, and storing; (2) The financial variable that relatecost of good manufactured Klbr-1 stoneware was Rp 1.605,67 each kg, that followby : raw material cost Rp 838,16, direct labor cost Rp 262,26, variable overheadcost Rp 90,30, and fixed overhead cost Rp 414,95. The cost price theoreticallysupply was Rp 1.846,52 each kg, that follow by : cost of good manufactured Rp1.605,67, expected profit margin Rp 80,26, marketing expense Rp 96,34, and general& administration expense Rp 64,22; and (3) The marketing mix of Klbr-1 stonewarewas still simple and was not comercially. Products still research stage that was notsupply on business, price was not competitive perfectly that setting depend on cost ofgood manufactured, promotion was not act professionally which itsapplication stillby self employee, and distribution still use self transportation tools that directly.